PEMODELAN FAKTOR – FAKTOR YANG MEMPENGARUHI ANGKA HARAPAN HIDUP (AHH) DI JAWA TIMUR TAHUN 2022 - Erika Zahra Fitriananta; Pingky Febriyanti; Gangga Anuraga (LPPM Universitas PGRI Adi Buana, 2024)
AbstractThe Life Expectancy in East Java in 2022 reached 71.74, showing an increase from the previousyear. Several key factors influence the high or low life expectancy, including health indicators,environmental conditions, and socio-economic factors. To address issues related to life expectancy,one step taken is to identify the factors that significantly affect life expectancy. This study aims toidentify the factors that have a significant impact on life expectancy in East Java Province using aspatial regression approach. The analysis reveals that the Spatial Autoregressive (SAR) model isthe best with an AIC of 123.26. Significant factors in life expectancy include the proportion of thepopulation with national health insurance for the poor (????1) and the average years of schooling(X3).Keywords: Life Expectancy, East Java, Spatial Autoregressive (SAR).